CIRCUMCISION IN MALES WITH BLEEDING DISORDERS - Hassan Mansouritorghabeh; Abdollah Banihashem; Alireza Modaresi; Lida Manavifar (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Male circumcision practice is an invasive procedure that is using worldwide. It makes challenges to haemostatic system and its possible haemorrhagic side effects are more serious in bleeding individuals than normal subjects. In most cases, it can be complete controlled using infusion of appropriate amount of coagulation factors before and post circumcision.